Introducing Schizandra chinensis into the Southern Urals - Roza A. Bilalova (RUDN Journal of Agronomy and Animal Industries, 2022)
Long-term introduction of Schizandra chinensis (Turcz.) Baill. was studied studying. The aim of the research was to assess the introduction resistance of Schisandra chinensis from the collection of lianas of South-Ural Botanical Garden-Institute, Ural Federal Research Center of the Russian Academy of Sciences. The 7 phenological growth stages were studied in 2014-2021. The prospects for introduction were determined according to P.I. Lapin and S.V. Sidneva, introduction resistance was assessed by the method of N.V. Trulevich. The following parameters were assessed: completeness of shoot development cycle, stability of rhythmic processes, vital state, life form, rate of ontogenesis, and renewal. According to the results of the research, lemongrass plants successfully passed the introduction tests. The species stably goes through all phases of seasonal development under cultivation, it is adapted to local climatic conditions and has high winter hardiness. Moreover, Schizandra chinensis is highly decorative throughout the growing season (more than 5 months). In accordance with the integral assessment, the taxon is assigned to the first group of prospects for introduction; Schisandra chinensis is a resistant plant. The crop is promising for use in recreational areas of Ufa and other settlements of the Southern Urals.